A estrutura das representações sociais de estudantes de um curso de ciências biológicas sobre biólogo e professor - Krützmann, Fábio Luis (2019)
This dissertation investigated the structures of the Social Representations of the students of the Course of Biological Sciences of the Federal University of Santa Maria (UFSM) on the future positions: teacher and biologist. Using the theory of Social Representations of Serge Moscovici as a theoretical and methodological contribution, we seek to analyze the representations of the students as a social construction, having as support of the identities and the undergraduate degrees in common. Using questionnaires we obtained information about the profile of the students of this course (Age, gender and work), and their representations of future professional activities through a Free Association of Words (ALP). In the years 2016, 2017 and 2018 we applied these questionnaires for freshmen and graduate students of the course, for bachelor and future teachers students. A total of 190 students participated, mostly women (67%), with an average age of 22 years and only 7% are working. Using the software OPENEVOC 0.84, we separated the words through their frequencies and Average Order of Importance. We have assembled 332 different words that help characterize the professional identity of academics from the inductive terms "teacher is" and "biologist is". When asked about biologist answers orbit around the words researcher, curious, love, and important. While the answers to teacher focused on educator, teach and essential. We conclude that the social representations of the students indicate substantial differences between freshmen and graduate students, evidencing the importance of the course in the process of socialization and construction of representations about future professions, including professional identity.